1993
DOI: 10.3109/09513599309152510
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, cycle control and side-effects of two monophasic combination oral contraceptives: Gestodene/ethinylestradiol and norgestimate/ethinylestradiol

Abstract: Two monophasic oral contraceptives containing gestodene (GTD, 75 micrograms) and ethinylestradiol (EE, 30 micrograms) or norgestimate (NGS, 250 micrograms) and EE (35 micrograms) were compared during the first six cycles of use. The subjects were randomly assigned to receive either type: 97 received GTD/EE and 92 NGS/EE. Six women in the GTD/EE group and nine in the NGS/EE group withdrew from the study; three (3%) and two (2%), respectively, withdrew because of adverse reactions. A total of 562 cycles for GTD/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Endrikat [19] reported both intention-to-treat as well as valid case analysis. The type of analysis was unclear in two studies [18,28]. Post randomization exclusions were not mentioned in fifteen trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endrikat [19] reported both intention-to-treat as well as valid case analysis. The type of analysis was unclear in two studies [18,28]. Post randomization exclusions were not mentioned in fifteen trials.…”
Section: Resultsmentioning
confidence: 99%
“…This comparison is based on the single study by Affinito [18], including 174 women. No pregnancies were reported in either group at six months of OC use.…”
Section: Resultsmentioning
confidence: 99%
“…Randomized trials of currently available low‐dose COCs containing ethinylestradiol and different progestins given in cyclical regimens were compared in terms of contraceptive effectiveness, cycle control, and side effects, including headache. Of 30 studies including in the review, 17 reported headache 41‐57. None of the studies reviewed found that any of the progestins compared affected either risk of headache (Supporting Information Table S4) or discontinuation of the COC as a result of headache (Supporting Information Table S5) …”
Section: Effect Of Contraceptive Methods On Headachementioning
confidence: 99%
“…None the studies analyzed found any clinically significant changes in ambulatory blood pressure in the subjects during monophasic EE/NGM treatment [47,50,[59][60][61]. The same trend was observed with the triphasic formulation [49,61].…”
Section: Blood Pressurementioning
confidence: 78%
“…Discontinuation because of weight gain during monophasic EE/NGM versus EE/NGL was observed in two different clinical trials: both samples demonstrated a slightly higher rate of discontinuation with NGL (1.4% with EE/NGL versus 1% with EE/NGM, by Corson [50]; 1.54% versus 0.84%, by Andolsek [58]). There were no significant changes in body weight at the end of 6 cycles in a comparative study by Tantbirojn et al (EE/LNG vs. EE/NGM) [59] and of a comparative study by Affinito et al between EE/ GSD and EE/NGM formulations [60]. The triphasic formulation EE/NGM showed the same moderate effects on body weight [49], with a similar effect in comparison with EE/LNG [61].…”
Section: Body Weightmentioning
confidence: 79%